The Effect of Addition of Bread Yeast and Time of Fermentation on the Characteristics of Vinegar from Palm Sap (Borassus flabellifer Linn) - Solo, Antonius; Ganda Putra, G.P.; Suparthana, I Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2020)
Indonesia's natural resources are rich in biodiversity which is a very prospective potential to be developed. One of them is palm tree. The main result of palm tree was sap. Palm sap can be processed into sugar or vinegar. This study aims to know the effect of addition of bread yeast and fermentation time on the characteristics of vinegar, determine the best treatment of adding bread yeast and fermentation time to produce vinegar from sap palm (Borassus flabellifer Linn), and to know the stability of vinegar products for storage temperature. The experimental design used was factorial Completely Randomized Design with 2 factors, namely the addition of bread yeast (0%, 1%, 2%, 3%, 4% and 5%) and fermentation time (0, 10, 15, 20, 25 and 30 days). The data obtained were analyzed by ANOVA and if the treatment had a significant effect it was followed by the Duncan test. The results showed that (1) the treatment of adding bread yeast had an effect on acetate levels, alcohol content, total soluble solids and pH; but does not affect total sugar; fermentation time affects the level of acetic acid, total sugar, alcohol content, total soluble solids and pH; while the interaction between treatments has an effect on total soluble solids and pH, but does not affect acetic acid levels, total sugar and alcohol content on vinegar from fermented of palm sap, (2) treatment of addition of 5% bread yeast with 30 days fermentation time was the best treatment for producing vinegar, with characteristics of acetic acid level of 2.72% v / v, total sugar 0.03%, alcohol content 0.68% and total soluble solids 2.60 °Brix; (3) the stability of vinegar products produced at various storage temperatures an affects the levels of acetic acid and total soluble solids.